Anscombe and the Unity of “Intention” - Noam Melamed (Enrahonar: Quaderns de Filosofia, 2020)
The conviction that ‘intention’ is not semantically ambiguous but has a single and distinctive meaning frames the argument of Anscombe’s masterwork Intention. What this meaning is, however, is barely recognizable in her book. One reason for this difficulty is that Intention starts from a threefold division of the appearance of the concept in our natural language and proceeds to develop its various accounts piecemeal. Another is the obscurity of the notion of ‘practical knowledge’ it introduces, precisely for shedding the light that would make its topic perspicuous as a whole. The present article aims to amend this obscurity by providing both a schema of unity for the various parts of the division and an account of the fixed character of the concept. For the former task, the article recaptures Anscombe’s technical use of the term ‘a kind of statement’, uses it to clarify the nature of the division’s parts, and argues that they are co-constituted in a larger context of rational proceedings. Having done this, the article shows that the point of such proceedings is to display the validity of practical reasoning in a given case. It analyses Anscombe’s account of this kind of validity, providing thereby the representation of the fixed character of ‘intention’ as a distinct form of thinking.